Loss of EMILIN-1 Enhances Arteriolar Myogenic Tone Through TGF-β (Transforming Growth Factor-β)–Dependent Transactivation of EGFR (Epidermal Growth Factor Receptor) and Is Relevant for Hypertension in Mice and Humans. Issue 10 (October 2018) - Carnevale, Daniela; Facchinello, Nicola; Iodice, Daniele; Bizzotto, Dario; Perrotta, Marialuisa; De Stefani, Diego; Pallante, Fabio; Carnevale, Lorenzo; Ricciardi, Franco; Cifelli, Giuseppe; Da Ros, Francesco; Casaburo, Manuel; et al.
Abstract : Objective—: EMILIN-1 (elastin microfibrils interface located protein-1) protein inhibits pro–TGF-β (transforming growth factor-β) proteolysis and limits TGF-β bioavailability in vascular extracellular matrix. Emilin1 −/− null mice display increased vascular TGF-β signaling and are hypertensive. Because EMILIN-1 is expressed in vessels from embryonic life to adulthood, we aimed at unravelling whether the hypertensive phenotype of Emilin1 −/− null mice results from a developmental defect or lack of homeostatic role in the adult. Approach and Results—: By using a conditional gene targeting inactivating EMILIN-1 in smooth muscle cells of adult mice, we show that increased blood pressure in mice with selective smooth muscle cell ablation of EMILIN-1 depends on enhanced myogenic tone. Mechanistically, we unveil that higher TGF-β signaling in smooth muscle cells stimulates HB-EGF (heparin-binding epidermal growth factor) expression and subsequent transactivation of EGFR (epidermal growth factor receptor). With increasing intraluminal pressure in resistance arteries, the cross talk established by TGF-β and EGFR signals recruits TRPC6 (TRP [transient receptor potential] classical type 6) and TRPM4 (TRP melastatin type 4) channels, lastly stimulating voltage-dependent calcium channels and potentiating myogenic tone. We found reduced EMILIN-1 and enhanced myogenic tone, dependent on increased TGF-β-EGFR signaling, in resistance arteries from hypertensive patients. Conclusions—: Taken together, our findings implicate an unexpected role of the TGF-β-EGFR pathway in hypertension with current translational perspectives. Abstract : Supplemental Digital Content is available in the text.